Pengaruh Perencanaan Pajak (Tax Planning) Atas Aset Tetap Terhadap Laba Pada PT. Leading Garment Industries - Ono Tarsono (Jurnal Ekonomi, 2018)
PT. Leading Garment Industries is a company engaged in the manufacture of women's clothing and men. This study aims to determine whether the PT. Leading Garment Industries tax planning depreciation of fixed assets. The data used is the data and the company's fiscal period 2016-2014. In this study made calculations using the straight-line method. The data used in this research is secondary data, data analysis technique used is quantitative descriptive. The analysis concluded that there are differences in the calculation of depreciation of fixed assets in the fiscal and according to the company. Such differences result in the presentation of its income statement also different and influenced the net income in the company in 2016 before tax planning Rp. 101 273 003 after the tax planning Rp.17.895.860, 2011 before tax planning Rp. 91.87738 million after tax planning Rp. 1282454, 2012 before tax planning Rp. 79,890,799 after tax planning losses amounting to Rp. 20,105,701, 2013 before tax planning Rp. 262 776 230 after the tax planning Rp. 177 867 610, and the last in 2014 before tax planning amounted to Rp. 262 776 230 after the tax planning Rp. 177 867 610. an increase in depreciation costs could have an impact on the decrease in corporate profits that the company's profit as income tax base will be smaller.